A survey of coping strategies among clinical nurses in China during the early stage of coronavirus disease 2019 pandemic: A cross‐sectional study. Issue 6 (3rd May 2021) - Tang, Jiao; Zhang, You; Xiong, Fangfang; Li, Fuying; Zheng, Zehong; Gao, Xi; Luo, Zhongchen
Abstract: Aims: To investigate coping strategies and identify their associated factors among Chinese clinical nurses during the early stage of coronavirus disease 2019 pandemic. Design: A cross‐sectional study. Methods: This study was conducted in seven designated hospitals involved in the diagnosis and treatment of the coronavirus disease 2019 in the southwest of China between 1 February and 31 March, 2020. Multiple linear regression was conducted to explore the association of different factors with the coping strategies of nurses. Results: Nurses' positive coping was associated with higher psychological capital ( B = 0.185, 95% CI 0.158–0.213), social support ( B = 0.292, 95% CI 0.244–0.340) and lower frustration ( B = −0.065, 95% CI −0.123 to −0.007). In contrast, higher frustration ( B = 0.091, 95% CI 0.044–0.139), lower performance ( B = −0.054, 95% CI −0.101 to −0.007) and psychological capital ( B = −0.035, 95% CI −0.055 to −0.014) were associated with negative coping.